Frequency of Nasal Carriage of Staphylococcus Aureus and Its Antimicrobial Resistance Pattern in Patients on Hemodialysis (Iranian Journal of Kidney Diseases, 2010)
Introduction. Staphylococcus aureus is currently the most common cause of infection in hospitalized patients. Patients on hemodialysis are at increased risk due to their immunocompromised state. The present study was designed to determine the frequency of S aureus nasal carriage in patients on hemodialysis.Materials and Methods. This study was undertaken in 2 dialysis centers to establish the frequency of S aureus nasal carriage at teaching hospitals of Mazandaran University of Medical Sciences, in the north of Iran. Standardized nose swabs were rotated into the anterior nares of the patients, and the samples were cultured on a blood-agar medium. Having grown the colony, gram stain, catalase, manitol, DNAase, and coagulase tests were all performed. Pattern of antibacterial sensitivity was determined by using the disc diffusion method. Also, agar dilution method was used to determine minimal inhibitory concentration of oxacillin and vancomycin.Results. Of 84 patients on hemodialysis, 31 (36.9%) were nasal carriers of S aureus, of whom 23 (74.2%) were resistant to methicillin. Of the methicillin-resistant S aureus isolates, 3 (13.0%) were resistant to vancomycin and 7 (56.5%) had reduced susceptibility to vancomycin in agar dilution method. Resistance frequencies to clindamycin, ciprofloxacin, and trimethoprim-sulfamethoxsazole were 12.9%, 9.7%, and 19.3%, respectively. However, all microorganisms were sensitive to rifampicin.Conclusions. Patients on hemodialysis are at an increased risk of S aureus infections; thus, screening of these susceptible patients should be considered as a health priority. Meanwhile, microbial sensitivity tests should be ordered for all cases in order to optimize treatment options.